Solomon to the exile studies in Kings and Chronicales - Whitcomb John C., Jr. (Grand Rapids, MI Baker, 1971)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Kings -- commentaries; Bible. O.T. Chronicals -- commentaries